Cross-Border Parcel Delivery Prices: Intuitions drawn from the world of telecommunications - J. Scott Marcus; Georgios Petropoulos (International Telecommunications Society (ITS), 2016)
In its Digital Single Market (DSM) strategy, the European Commission has rightly noted the importance of lowering the price paid for basic cross-border delivery by consumers and by small and medium size retail shippers. Consumers and SMEs may have few alternatives to the National Postal Operators (NPOs), or may be unaware of the options that they have. These concerns led to the Commission to put forward a legislative proposal in May 2016.3 With its legislative proposal, the Commission has sought (1) to strengthen the data gathering powers of Member State postal regulatory authorities, and to oblige them to collect data at both retail and wholesale levels; (2) to increase transparency into pricing for those who use cross-border parcel delivery services; (3) to oblige Member State postal regulatory authorities to assess annually the affordability of these services; and (4) to open cross-border Terminal Dues (TD) and Inward Land Rates (ILR) arrangements to competitors There are parallels that can be drawn between the payment flows for cross-border parcel delivery and those of telecommunications, especially those of international mobile roaming. As with roaming, it is clear that the linkages between wholesale payments between and corresponding retail prices need to be properly understood in order to craft good policy. Another useful lesson is that Member State postal regulatory authorities are unlikely to address cross-border problems not only because of limitations in their respective mandates, but also because they have no incentive to take challenging measures to benefit residents of other countries. There are, however, also important differences between roaming versus parcel delivery. Where high wholesale charges were a major driver of high retail prices for international mobile roaming, the wholesale payments for cross-border parcel delivery appear instead to be below cost. This implies that it is the “spread” between retail price and the wholesale payment that is inflated, at least for small retail shippers and for consumers. Reviewing the Commission's proposed Regulation with all of this in mind, it appears to be on target. The main question that remains open is whether NPOs will be able to adjust TD and ILR rates upward to reflect true costs, as they will be strongly motivated to do; here as well, however, there are grounds for cautious optimism.
Keywords: 330